Assessing the sustainability of the city-port transformations: Multi-Criteria Decision Analysis (MCDA) for alternatives portfolio selection [Valutare la sostenibilità delle trasformazioni città- porto: Analisi Decisionale Multi-Criteriale (MCDA) per la selezione di un portafoglio di alternative] - Simona Panaro; Giuliano Poli; Marilisa Botte; Sabrina Sacco; Maria Cerreta (Valori e Valutazioni, 2023)
In recent years, the EU has sought to define sustainable transition pathways towards more equitable, prosperous, and inclusive urban and territorial models, capable of responding to the rapid degradation of ecosystems, and improving quality of life of citizens. In this context, ports have been recognised as key strategic hubs not only for economic and logistical competitiveness, but also to generate employment and investment opportunities, and to address the challenges of the climate change. The research presents a multi-scale, multi-dimensional and multi- group methodological framework to support decision-making processes related to the development of sustainable transformations of port cities, capturing the complexity of interactions and conflicts. Integrating Multi-Criteria Decision Analysis (MCDA) approaches and Problem Structuring Methods (PSM), the proposed methodology aims to address the following gaps identified in the literature: (i) a scattered application of multi-group methods; (ii) the lack of social instances within the decision problem; (iii) a weak sustainability perspective; (iv) the use of one-dimensional scale assessment in sectoral studies. The case study of the city-port of Gela in Sicily (Italy) provided an opportunity to test the proposed methodology and to integrate multi-dimensional sustainability issues into feasibility studies, promoting a more balanced relationship between city and port. The interdependencies between environment, society and economy allowed MCDA to be identified as a suitable approach to address complex decision-making and support the sustainability assessment of port areas transformation. Two multi-criteria and multi-group evaluation methods guided the decision-making process to select a portfolio of preferred alternatives by assessing technical, environmental, and economic impacts and analysing stakeholder conflicts and coalitions. The process was carried out as follows: on the one hand, a multidimensional impact matrix integrating Key Performance Indicators (KPIs) divided into technical, financial-economic, and environmental categories through the application of the multi-criteria method EVAMIX; on the other hand, a social assessment with a dendrogram of coalitions derived from the application of the multi-group method NAIADE by modelling stakeholders’ preferences regarding a portfolio of alternatives related to the decision problem.